A var gene promoter implicated in severe malaria nucleates silencing and is regulated by 3’ untranslated region and intronic cis-elements - Muhle, Rebecca A. (2009)
Questions surround the mechanism of mutually exclusive expression by which Plasmodium falciparum mediates activation and silencing of var genes. These encode PfEMP1 proteins, which function as cytoadherent and immunomodulatory molecules at the surface of parasitized erythrocytes. Current evidence suggests that promoter silencing by var introns might play a key role in var gene regulation. To evaluate the impact of cis-acting regulatory regions on var silencing, we generated P. falciparum lines in which luciferase was placed under the control of an UpsA var promoter. By utilizing the Bxb1 integrase system, these reporter cassettes were targeted to a genomic region that was not in apposition to var sub-telomeric domains. This eliminated possible effects from surrounding telomeric elements and removed the variability inherent in episomal systems. Studies with highly synchronized parasites revealed that the UpsA element possessed minimal activity in comparison with a heterologous (hrp3) promoter. This may well result from the integrated UpsA promoter being largely silenced by the neighboring cg6 promoter. Our analyses also revealed that the DownsA 3’ untranslated region further decreased the luciferase activity from both cassettes, whereas the var A intron repressed the UpsA promoter specifically. By applying multivariate analysis over the entire cell cycle, we confirmed the significance of these cis-elements and found the parasite stage to be the major factor regulating UpsA promoter activity. Additionally, we observed that the UpsA promoter was capable of nucleating reversible silencing that spread to a downstream promoter. We believe these studies are the first to analyze promoter activity of Group A var genes which have been implicated in severe malaria, and support the model that var introns can further suppress var expression. These data also suggest an important suppressive role for the DownsA terminator. Our findings imply the existence of multiple levels of var gene regulation in addition to intrinsic promoter-dependent silencing.